Межі (без)компромісності: Олесь Гончар у рецепції Івана Кошелівця - Тарнашинська, Л.Б. (Слово і Час, 2019)
У статті простежено рецепцію романістики О. Гончара на сторінках журналу “Сучасність” у 1960 – 1990 рр. Дослідниця вибудовує свою статтю на різножанрових публікаціях І. Кошелівця, підкріплюючи спостереження міркуваннями відомих літературознавців щодо специфіки інтерпретації тексту. Сповідуючи презумпцію факту та художньо-естетичні критерії поцінування художнього тексту, критик із Заходу висновував свої сентенції на історичному тлі та в широкому європейському літературному контексті. Обстоюючи свою антикультівську позицію щодо О. Гончара, він оцінював твори класика української радянської літератури виключно з позиції художньої правди. Ця контроверсійна тема в опозиційному літературно-критичному дискурсі І. Кошелівця тривалий час сприймалася своєрідним викликом, підривом “основ” національної культури, однак без її детального розгляду історія української літератури буде неповною. The paper traces the reception of O. Honchar’s personality and works in publications of the journal “Suchasnist” in 1960s–1990s. The author of the paper bases her research on the multi-genre publications by I. Koshelivets, which had utterly polemical tone, and reinforces her observations with the other scholars’ ideas regarding the specifics of interpreting the text. Adhering to the presumption of fact and the aesthetic criteria for assessing the work of literature, a Western critic put his maxims against a historical background and in a broad European literary context. Defending his anti-cult position in regard to the writer’s personality of O. Honchar, I. Koshelivets evaluated the works of the Ukrainian Soviet literature classic based on the ground of artistic truth exclusively. Despite the fact that O. Honchar mastered the language skillfully and had an indisputable gift of a writer, he always adhered to the ‘boundaries of the permitted’, which made him to limit the scope of themes and adhere to the artificial style with its varnished reality and false poetic flavor. Paying tribute to the fact that O. Honchar supported the Ukrainian sixtiers and always had a pro-Ukrainian position, I. Koshelivets still kept his principled position for decades. The critic considered the literary work of O. Honchar as a sample of socialist realism with its indisputable taboos. In particular, he analyzed in detail the most known Honchar’s novel “Cathedral”. According to I. Koshelivets, it got its fame mostly due to the party functionaries that made a relatively weak piece of literature a political event and gave it some extra-literary value, so that the issues of style and literary features became secondary. The author of the paper states that in the conditions of a totalitarian society and ideologically controlled literary process, the talent of O. Honchar couldn’t be realized properly, anyway. This controversial topic of I. Koshelivets’s interpretation of the works by Ukrainian Soviet literature classic has been perceived within the oppositional literary-critical discourse as a kind of challenge undermining the ‘foundations’ of the national culture. Although without its detailed consideration the history of Ukrainian literature will be incomplete.